Antenatal sonographic assessment of cross sectional area of umbilical cord components and its reference value in normal pregnancy - Afroze, Khizer Hussain; Subash, Lakshmiprabha; H., Anand S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Measuring the cross-sectional area of umbilical components in normal pregnant women helps in assessing the fetal abnormalities. Very few literatures were available on evaluation of reference values of cross sectional areas of umbilical cord components. The present study was conducted with the aim to determine the normal reference values of cross sectional areas of umbilical arteries, umbilical vein and Wharton’s jelly and to correlate them with the gestational age of the fetus. Methods: A cross sectional study was conducted on 300 normal pregnant women at the Department of Radiodiagnosis, Sri Siddhartha Medical College, Tumakuru, Karnataka to assess the reference range of cross sectional areas of umbilical cord arteries, umbilical vein and Wharton’s jelly at different gestational age of the fetus to analyze their growth. Results: A statistically significant correlation was observed between cross sectional areas of umbilical artery and vein and gestational age before and after 34 weeks (p=0.005 and 0.006 respectively) but no significant correlation was noticed with the cross-sectional area of Wharton’s jelly (p=0.088). Conclusions: Cross sectional area measurements of umbilical cord components can be considered as important tools for estimation of fetal growth.